Surgical and non‐surgical interventions for primary and salvage treatment of growth hormone‐secreting pituitary adenomas in adults - Caulley, Lisa (Cochrane Database Syst Rev, 2020)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of surgical and non‐surgical interventions for primary and salvage treatment of GH‐secreting pituitary adenomas in adults.